Debating Gandhi - Basham, A. L.; Raghuramaraju, A. (Oxford University Press, 2006)
Brings together significant essays on Gandhi by noted Indian scholars including A L Basham, Ashis Nandy, Bhikhu Parekh among others. This volume attempts to reassess the continuing relevance of Gandhi.